Macrophage-Specific Cathepsin as a Marker Correlated with Prognosis and Tumor Microenvironmental Characteristics of Clear Cell Renal Cell Carcinoma - Zhang F; Liang J; Lu Y; Tang Y; Liu S; Wu K; Zhang F; Lu Y; Liu Z; Wang X (Dove Medical Press, 2022)
Fan Zhang,1,* Jiayu Liang,1 You Lu,2,* Yongquan Tang,3 Shengzhuo Liu,1 Kan Wu,1 Fuxun Zhang,1 Yiping Lu,1 Zhihong Liu,1 Xianding Wang1 1Department of Urology, Institute of Urology, West China Hospital, Sichuan University, Chengdu, 610041, People's Republic of China; 2Department of Pediatrics, West China Second University Hospital, Chengdu, Sichuan University, Chengdu, 610041, People's Republic of China; 3Department of Pediatric Urology, West China Hospital, Sichuan University, Chengdu, 610041, People's Republic of China*These authors contributed equally to this workCorrespondence: Xianding Wang; Jiayu Liang, Email xiandingwang66@126.com; drliangjiayu@163.comBackground: Cathepsin Z (CTSZ) is a cathepsin family member that plays a dual role in the adhesion and migration of immune and tumor cells.Methods: The expression pattern of CTSZ in clear cell renal cell carcinoma (ccRCC) was observed by immunohistochemistry and validated by using double-labeling immunofluorescence. Publicly available single-cell sequencing data was used to further define the cell type-specific CTSZ expression in ccRCC. Methylation modification, immune infiltration, and tumor-related signaling enrichment analyses involving CTSZ were performed using multi-omics data. Data from two independent cohorts of anti-programmed death-1 (PD-1) therapeutic clinical trials were used to investigate correlations between CTSZ levels and treatment responses.Results: CTSZ was upregulated in ccRCC tissues compared with adjacent normal tissues at the RNA but not in ccRCC cells. Immunohistochemistry indicated that CTSZ was expressed in tumors infiltrated with lymphocytes. Double immunofluorescence demonstrated that CTSZ was co-expressed with CD68 but not CD8. Single-cell transcriptome data showed macrophage-specific expression of CTSZ in ccRCC. High CTSZ expression was significantly correlated with the enrichment of interferon-γ, epithelial‐to‐mesenchymal transition, cell cycle, apoptosis pathways, and B cell, macrophage, neutrophil, and dendritic cell infiltrations, as well as the expression of immune checkpoints CTLA4, LAG3, HAVCR2, PDCD1LG2, PDCD1, TIGIT, and SIGLEC15. Hypomethylation modification of cg02744249, cg02744249, and cg22145559 were negatively correlated with CTSZ expression, suggesting an epigenetic mechanism for the regulation of CTSZ expression. Clinically, CTSZ levels were associated with the prognosis of patients with ccRCC (hazard ratio=1.5, P=0.007). Notably, patients with higher CTSZ expression had a worse prognosis with anti-PD-1 monotherapy (hazard ratio=1.51, P=0.039).Conclusion: Macrophage-specific CTSZ was associated with activation of epithelial‐to‐mesenchymal transition, cell cycle signatures, and a higher infiltration level of B cells, macrophages, neutrophils, and dendritic cells in the tumor microenvironment. High expression of CTSZ could be considered as a prognostic and treatment response biomarker for patients with ccRCC receiving anti-PD-1 immunotherapy.Keywords: ccRCC, CTSZ, macrophage, single-cell, prognosis